"Understanding Human Decision-Making: The Interdisciplinary Insights of Behavioural Economics" - Sonam Arora, Arti Kumari (European Economic Letters (EEL), 2024)
Behavioural economics is the interaction of psychological science, neuroscience, sociology, and classical economics as applied to analysing how actual human behaviour differs from models expected on the basis of neo-classical economic theory. While neoclassical economics takes the assumption of rational behaviour, availability of full information and consistent utility maximisation as premises for analysing choices, behavioural economics explores how individual determination, systematic distortion in perception, feelings and social factors systematically influence the decision-making processes. Important models: The use of ‘prospect theory’ indicates how actors perceive certain changes in their payoff situation in terms of differences from some reference point and exhibit ‘loss aversion’. Heuristics are also included because while they streamline the decision process, they include the availability bias – estimating events’ frequencies based on the amount of recent exposure, and representativeness bias – estimating probabilities based on similarity. Other core concepts are: Bounded rationality, it means that due to special conditions it’s difficult to process information; Status quo bias, it means people prefer such values of different indicators, which happened to be preferable in the past; Hyperbolic discounting, it is when people overestimate the utility of the immediate reward comparing to the one received at the later time. The requirements of touch, association, and belonging are also an important aspect in the model Human social and emotional factors social and emotional factors. Behavioural economics studies events like giving, giving back and the effects of social expectations and compliance. It also shows how external stimuli, proximal effects and even so-called ‘biases’ can shape choices ranging from saving to an organ donor choice through the use of defaults. This field has a broad relevance; it can be used in policy analysis, medicine, accounting, commercial promotion, and environmental concern among others. For example, behavioural interventions have been applied to enhance retirement saving, medication taking and energy saving. As a theory, behavioural economics gives better insights of human behaviour to allow suite plans to be made for the ways that human beings behave thereby providing powerful instruments for bettering individual and public results.